Critical evaluation of arguments opposing male circumcision: A systematic review. Issue 4 (8th September 2019) - Morris, Brian J; Moreton, Stephen; Krieger, John N
Abstract: Objective: To systematically evaluate evidence against male circumcision (MC). Methods: We searched PubMed, Google Scholar, EMBASE and Cochrane databases. Results: Database searches retrieved 297 publications for inclusion. Bibliographies of these yielded 101 more. After evaluation we found: Claims that MC carries high risk were contradicted by low frequency of adverse events that were virtually all minor and easily treated with complete resolution. Claims that MC causes psychological harm were contradicted by studies finding no such harm. Claims that MC impairs sexual function and pleasure were contradicted by high‐quality studies finding no adverse effect. Claims disputing the medical benefits of MC were contradicted by a large body of high‐quality evidence indicating protection against a wide range of infections, dermatological conditions, and genital cancers in males and the female sexual partners of men. Risk‐benefit analyses reported that benefits exceed risks by 100‐200 to 1. To maximize benefits and minimize risks, the evidence supported early infant MC rather than arguments that the procedure should be delayed until males are old enough to decide for themselves. Claims that MC of minors is unethical were contradicted by balanced evaluations of ethical issues supporting the rights of children to be provided with low‐risk, high‐benefit interventions such as MC for better health. Expert evaluations of case‐law supported the legality of MC of minors. Other data demonstrated that early infant MC is cost‐saving to health systems. Conclusions: Arguments opposing MC are supported mostly by low‐quality evidence and opinion, and are contradicted by strong scientific evidence.